2016
DOI: 10.1007/978-3-319-31248-4_9
|View full text |Cite
|
Sign up to set email alerts
|

How to Manipulate the Microbiota: Prebiotics

Abstract: During the last century, human nutrition has evolved from the definition of our nutritional needs and the identification of ways to meet them, to the identification of food components that can optimise our physiological and psychological functions. This development, which aims to ensure the welfare, health and reduced susceptibility to disease during life, gave birth to the concept of "functional foods". In this context, there is an increasing interest in the physiological effects induced by the dense and dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 123 publications
1
56
0
7
Order By: Relevance
“…This need was amplified by views that the pre biotic concept required clarification on specificity, mech anisms of effect, health attributes and relevance, with some authors being critical of concepts already put forward and its approaches [24][25][26] . Thus, the current ISAPP consensus panel now proposes the following definition of a pre biotic: a substrate that is selectively utilized by host micro organisms conferring a health benefit…”
Section: Evolution Of the Term Prebioticmentioning
confidence: 99%
“…This need was amplified by views that the pre biotic concept required clarification on specificity, mech anisms of effect, health attributes and relevance, with some authors being critical of concepts already put forward and its approaches [24][25][26] . Thus, the current ISAPP consensus panel now proposes the following definition of a pre biotic: a substrate that is selectively utilized by host micro organisms conferring a health benefit…”
Section: Evolution Of the Term Prebioticmentioning
confidence: 99%
“…135 Given the beneficial effects of microbial fermentation products such as butyrate, many strategies are designed to increase the production of this metabolic product and other short chain fatty acids. Because such treatments presume that the appropriate microbes are present, a variation is to administer a "synbiotic" containing both the relevant probiotic organism and prebiotic carbohydrate.…”
Section: Prebiotics and Diet Therapymentioning
confidence: 99%
“…They consist the "food" to grow more probiotic strains in order to enhance the health of the host. The beneficial abilities of probiotics and prebiotics in connection with the modulation of intestinal microbiota, the immunomodulation and the strengthening of the epithelial barrier [50][51][52] . Study that was contacted on specific pathogen-free conditions (SPF) HLA-B27 transgenic rats, showed that a combination of chicory-derived long-chain inulin and oligofructose (Synergy -1) reduced the development of intestinal inflammation 53 .…”
Section: Probiotics And/or Prebiotics As Therapeutic Treatment Of Asmentioning
confidence: 99%